Soybean Production in Florida - David L. Wright; Jimmy R. Rich; James J. Marois; Richard K. Sprenkel (EDIS)
This document is SS-AGR-182, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2002.